Výpočetní re-fotografie - Červenka, Adam (Vysoké učení technické v Brně‎, Antonínská 548/1, 601 90 Brno, http://www.vutbr.cz/, 2017)
Photographing by historical picture is subject of interest both for photographers and researcher. In this way, it is possible to observe development of site, or its surroundings, within the timeframe. Problem may come to pass when we want to found the same view as the reference picture. Finding the same view is usually solve only by manually.  In this case, photographers must rely to estimation and photographic skill. This method may be inaccurate and for photographer considerably inconvenient. The solution is the refutographic algorithm that using computer vision techniques.
Keywords: Real-time aplikace; Rephotography; 3D rekonstrukce; Android OS; 3D reconstruction; OpenCV; Refotografie; Real-time application